2004
DOI: 10.3758/bf03196625
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory reflected in printed word naming

Abstract: Although memory is typically measured by recall or recognition, it is also expressed by fluent or stylized task performance. In this experiment, 12 volunteers (called speakers) completed four experimental stages over a 2-week period. They read printed words aloud in two sessions, before and after exposure to auditory training tokens. They later completed a recognition memory test, discriminating old from new words. Groups of perceptual judges assessed the speakers' vocal imitation by comparing utterances recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 35 publications
7
86
4
Order By: Relevance
“…This effect of word frequency on rated convergence is consistent with the past literature (e.g., Goldinger, 1998;Goldinger & Azuma, 2004; but see Pardo et al, 2013). The lexical model also revealed ratings of convergence to be greater for low-density (M = .710) than for high-density (M = .664) words, 尾 = 0.280, SE = 0.093, Z = 3.019, p < .003.…”
Section: Lexical Influencessupporting
confidence: 79%
See 2 more Smart Citations
“…This effect of word frequency on rated convergence is consistent with the past literature (e.g., Goldinger, 1998;Goldinger & Azuma, 2004; but see Pardo et al, 2013). The lexical model also revealed ratings of convergence to be greater for low-density (M = .710) than for high-density (M = .664) words, 尾 = 0.280, SE = 0.093, Z = 3.019, p < .003.…”
Section: Lexical Influencessupporting
confidence: 79%
“…Our experiments also tested word stimuli that systematically varied in both their word frequency and phonological neighborhood density characteristics, consistent with some previous convergence studies (e.g., Goldinger, 1998;Goldinger & Azuma, 2004;Pardo, Jordan, Mallari, Scanlon, & Lewandowski, 2013). Perceivers have previously been found to converge more to the spoken utterances of words with lower frequencies of occurrence within the English lexicon (Goldinger, 1998;Goldinger & Azuma, 2004).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In what is known as a shadowing task or an auditory naming task where participants simply repeat single words after a model talker, Goldinger (1998) found that when participants repeat words, they acquire phonetic aspects of the model talker's voice. This general finding has been well replicated (Namy, Nygaard, & Sauerteig 2002, Goldinger & Azuma 2004. In the completion of a conversational map task, speakers were also found to converge phonetically on each other's productions; the direction of the convergence though was influenced by several social factors, namely gender and participant role (Pardo 2006).…”
supporting
confidence: 60%
“…There is considerable evidence that these encodings continue to play a role in adults' ongoing perception of language. That is, adults use far more fi ne phonetic detail in ongoing speech perception than can be captured in even detailed categorical phonetic transcriptions (e.g., Goldinger and Azuma 2004;McLennen and Luce 2005). The second is that phonological generalizations should track the statistics of the lexicon.…”
Section: A Proposalmentioning
confidence: 99%